Effectiveness of atrial fibrillation on high-intensity transient signals to cerebral circulation during TAVI. (14th October 2021) - Kalantzis, C; Vavuranakis, M A; Voudris, V; Kosmas, E; Kalogeras, K; Bei, E; Katsianos, E; Siasos, G; Tousoulis, D; Tsioufis, C; Vavuranakis, M
Abstract: Background: Cerebral microemboliazations remain a major concern peri-operatively and following Transcatheter Aortic Valve Implantation (TAVI). We evaluated whether atrial fibrillation may predispose to an increased number of cerebrovascular emboli during the procedure. Purpose: The aim of the study was to evaluate, using a transcranial doppler, the effect of atrial fibrillation on transient high-intensity signals to middle cerebral arteries during transcatheter aortic valve implantation. Methods: Consecutive patients who underwent transfemoral TAVI with Evolut™ R bioprosthesis, were categorized into two groups. Group A patients with permanent atrial fibrillation (AF) on anticoagulation, Group B patients with sinus rhythm (SR). Dual antiplatelet therapy with aspirin and clopidogrel was administered to all patients 24 hours prior to the procedure at loading dose, with patients in Group A receiving in addition low-molecular-weight-heparin. The number of detected High Intensity Transient Signals (HITS) was assessed using Rimed Digi-Lite™ Transcranial Doppler on both cerebral arteries during the following phases of the procedure; Phase 0: 30 minutes prior to procedure initiation, Phase I: between access site puncture and introduction of the delivery system, Phase II: during the implantation of the bioprosthesis, until the removal of the delivery system. All implantations were performed without predilation. Furthermore, patients were evaluated by neurologist before TAVI and on discharge day. Safety was evaluated according to VARC-2 criteria. Results: Twenty-eight patients were evaluated (81±6 years, 16 males (57.1%)). Group A had higher number of total (786±95 vs. 604±103, p=0.002) as well as Phase I HITS (393±94 vs. 285±86, p=0.002). One cerebrovascular event was recorded in Group A and one patient categorized to Group B developed major bleeding due to conversion to femoral surgical cut-down. The average number of received blood units, was higher in AF compared to SR Group (Group 1: 0.8±1.9 vs. Group 2: 0.5±0.7, p: 0.886), without however, reaching statistical significance. Conclusion: Patients with atrial fibrillation had larger burden of embolic HITS during TAVI indicating high risk patients for embolic cerebrovascular events. This may has implications for future strategies for cerebral embolic protection. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Ippokrateio General Hospital of Athens